Pergeseran Nilai Etik: Sebuah Refleksi Atas Perilaku Ketua Komisi Pemberantasan Korupsi Dalam Perspektif Etika Pemerintahan - Wa Ode Srijuna Ramayana (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Ethics is a foundation or guideline for human behavior in interacting with other humans. Apart from that, ethics as a standard of values in regulating human behavior is very important to apply in government administration. These ethical values ​​are expressed juridically in the form of a code of conduct that must be adhered to by every state administrator. KPK as one of the state administrators also has a code of conduct that regulates the behavior of each member of the Commission. However, as time went by, there was a shift in the ethical values ​​carried out by the KPK leadership. This research aims to describe the shift in ethical values ​​carried out by the KPK leadership. This research was conducted using library research methods. Based on the analysis carried out, it shows that repeated deviant behavior occurs due to the loss of a culture of shame and a lack of sense of responsibility towards the mandate that is carried out. As a result, this behavior has an impact on organizational performance which tends to become less agile, responsive and less accountable.